Students’ Speaking Ability at Ninth Grade of Junior High School Number 6 Jambi City - Mia Fadila; Efa Silfia; Ridho Praja Dinata (JELT: Journal of English Language Teaching, 2022)
This research was conducted with the aim of to know students’ speaking skills, especially in the component of speaking skills in the ninth grade of Junior High School 6 Jambi City. This research was designed using descriptive quantitative research methods. The population of this study was the ninth-grade students at Junior High School 6 Jambi City, and the sample was grade IX B students. This study uses a test as a research instrument. Then the test results are assessed. The test used is an oral test. The oral test is made with the theme of "My family" which is determined by this research. The learning method is through a speaking test in front of the class with the theme "My Family". The results of this study indicate the scores of the five components of speaking skills. The components of speaking skills are grammar, vocabulary, comprehension, fluency, and pronunciation. The findings of this study indicate that the mean overall component of speaking skill score is 1,60. In the grammar component, 3 or 8,33% of students scored in the poor categories, 7 or 19,44% of students scored in the fair categories, 18 or 50% of students scored in the good categories, and in the excellent are 8 or 22,22%. In the vocabulary component, no one got scored poor, students scored in the fair categories are 11 or 30,55%, 18 or 50% of students scored in the good categories, and students scored in the excellent categories are 7 or 19.44%. In the comprehension component, no one got scored poor, 7 or 19,44% of students scored in the fair categories, 14 or 38.88% of students scored in the good categories, and in the excellent categories 15 or 41,66%In the fluency component, no one got scored poor, students scored in the fair categories are 8 or 22,22%, 16 or 44,44% of students scored in the good categories, 12 or 33,33% of students scored in the excellent categories. In the pronunciation component, no one got scored poor, 8 or 22,22% of students scored in the fair categories, 11 or 30.55% of students scored in the good categories, and 17 or 47,22% of students scored in the excellent categories. The mean and percentage values explain that the speaking skills of class IX students, especially class IX B at SMP Negeri 6 Jambi City is very good.